Alpha-linolenic acid enhances the phagocytic and secretory functions of alternatively activated macrophages in part via changes to the oxylipin profile. (February 2020) - Pauls, Samantha D.; Rodway, Lisa A.; Winter, Tanja; Taylor, Carla G.; Zahradka, Peter; Aukema, Harold M.
Abstract: Alternatively activated macrophages are innate immune cells that contribute to resolution of inflammation and maintenance of homeostasis. Modulation of available fatty acid sources is thought to affect cellular physiology through a variety of mechanisms, including through alterations to the profile of oxygenated free fatty acid metabolites, called oxylipins, produced in a cell type specific manner. Here, we investigated how treatment with the plant-sourced omega-3 fatty acid α-linolenic acid (ALA) affects the oxylipin profile and functional capacity of a cell culture model of human alternatively activated (M2a-like) macrophages. In a targeted but unbiased screen, ALA enhanced the production of oxylipins from all polyunsaturated fatty acid (PUFA) precursors, with oxylipins derived from ALA being enhanced the most. Consistently, ALA treatment enhanced the expression of both cytoplasmic and calcium-independent phospholipase A2. At a functional level, ALA treatment increased phagocytic activity and altered production of the chemokine MCP-1 by M2a-like cells in a manner dependent on the time of treatment. ALA treatment during polarization increased MCP-1 secretion, which was sensitive to pharmacological inhibition of 15-LOX-1 by ML351. Thus, ALA modulates the phenotype of alternatively activated macrophages, likely through its own LOX-derived oxylipins and/or through general modulation of oxylipin biosynthesis. These effects likely contribute to the overall anti-inflammatory benefit observed with ALA supplementation.